Identify the second step in solving this equation for y

: −3(y + 6) = 21
. (1 point)
Responses

Subtract 6 from both sides.
Subtract 6 from both sides.

Divide both sides by −3
.
Divide both sides by negative 3.

Divide both sides by 6.
Divide both sides by 6.

Add 6 to both sides.

1 answer

To solve the equation \(-3(y + 6) = 21\), the first step is to divide both sides by -3 to isolate the term with \(y\). Therefore, the second step after that would likely involve simplifying the equation that results from that division.

Since there are no operations required after the division other than algebraic simplification, the next operation needed to isolate \(y\) would be to subtract 6 from both sides of the equation.

Thus, the correct response to identifying the second step in solving this equation for \(y\) is:

Subtract 6 from both sides.

Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions